A nursing intervention based on the Zentangle® method: Experiences of patients diagnosed with borderline personality disorder - Ana Morales-Alonso; Ángela Iglesias-; Miriam Alonso-Maza (Elsevier, 2024)
Objective: The application of the Zentangle® Method in relation to relaxation and well-being has not been tested in patients with borderline personality disorder (BPD). This study was to analyze the practising Zentangle® experience in patients with BPD. Methods: With a phenomenological interpretative approach, this qualitative study conducted semi-structured interviews with patients who participated in a 6-session Zentangle® program accomplished monthly over six months in a Personality Disorders Unit. A total of 15 patients were interviewed for this study. Smith, Flowers & Larkin method was applied for evaluation in the data analysis. Results: Based on our findings, three categories were extracted: As you sow, so shall you reap (participants reported improvements in concentration, relaxation, interpersonal relationships, and interaction with their environment as well as positive experiences toward acceptance and change); Many hands make light work (patients admitted feeling better in a group and developed group membership. They described how a group environment influences individual behavior); Drawing your own path (this method provides a medium for self-expression and self-knowledge through drawing, improving well-being through emotional expression, enhancing creativity, and increasing self-confidence). Conclusions: By practicing Zentangle®, patients achieve behavioral responses such as flexibility and adaptability, reaching greater emotional well-being through anxiety management, impulse control, learning to cope with problems, or improving self-esteem or concentration. Mental health nursing plays a critical active role in the comprehensive treatment of BPD, as well as the mobilization and coordination of complementary and diverse interventions.